Conserved Immune Activation and Compartment-Specific Dysregulation in Temporomandibular Joint Osteoarthritis Cartilage: A Cross-Species Transcriptomic Analysis - Dedi Sucipto; Cindy Susanti; Vidhya Sathyakirti (Phlox Institute: Indonesian Medical Research Organization, 2025)
Background: Temporomandibular joint osteoarthritis (TMJ-OA) is molecularly heterogeneous, and differences in tissue, species, and disease model complicate transcriptomic integration. Objective: This study aimed to identify conserved and compartment-specific transcriptional programs across complementary rabbit and rat TMJ-OA cartilage datasets. Methods: A targeted GEO screen identified rabbit post-traumatic TMJ-OA (GSE232867; paired condylar cartilage and superficial zone; three animals per condition) as the primary dataset and rat unilateral anterior crossbite TMJ-OA (GSE207461; three samples per condition) for pathway-level validation. Counts were filtered with edgeR, TMM-normalized, transformed with voom, and modeled with limma; rabbit analyses were blocked by animal. Differentially expressed features required BH-FDR < 0.05 and absolute log2 fold change >= 1. Ordered g:Profiler enrichment tested directional pathway concordance. Results: Rabbit condylar cartilage yielded 421 differentially expressed features (346 upregulated and 75 downregulated), the superficial zone yielded 180 (69 upregulated and 111 downregulated), and 135 showed a condition-by-compartment interaction. Immune-associated genes were prominent in condylar cartilage, whereas superficial-zone downregulation centered on mitotic programs. Only Morf4l2 met the strict rat threshold, but 13 upregulated pathways were concordant across species; leukocyte activation was strongest (conservative adjusted P = 2.16 x 10^-6). Conclusion: Pathway-level immune activation was the most reproducible signal across these animal TMJ-OA cartilage datasets, accompanied by compartment-specific proliferative dysregulation. Small preclinical bulk datasets preclude cell-specific or human inference.